2016
DOI: 10.1021/acs.est.6b03585
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Exhaust Emissions from Three Diesel-Hybrid Cars and Simulation of After-Treatment Systems for Ultralow Real-World NOx Emissions

Abstract: Hybridization offers great potential for decreasing pollutant and carbon dioxide emissions of diesel cars. However, an assessment of the real-world emissions performance of modern diesel hybrids is missing. Here, we test three diesel-hybrid cars on the road and benchmark our findings with two cars against tests on the chassis dynamometer and model simulations. The pollutant emissions of the two cars tested on the chassis dynamometer were in compliance with the relevant Euro standards over the New European Driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…It is a part of the EMEP/CORINAIR Atmospheric Emissions Inventory Guidebook used by EU member states for official air emission inventorying. COPERT is also widely used around the world in air quality studies and academic research (Fontaras et al, 2014;Franco et al, 2016;Lozhkin, 2015, Ni et al, 2018).…”
Section: Methodology and Input Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a part of the EMEP/CORINAIR Atmospheric Emissions Inventory Guidebook used by EU member states for official air emission inventorying. COPERT is also widely used around the world in air quality studies and academic research (Fontaras et al, 2014;Franco et al, 2016;Lozhkin, 2015, Ni et al, 2018).…”
Section: Methodology and Input Data Collectionmentioning
confidence: 99%
“…Monitoring and improving air quality in built environment and cities are of crucial importance in the Russian Federation and all over the world (Franco et al, 2016;Genikhovich and Sciermeier, 1995;Genikhovich et al, 2002;Jain and Tiwari, 2016;Khreis et al, 2018;Lehtomäki et al, 2018;Lozhkin et al, 2013;Ni et al, 2018;Silva and Mendes, 2012;Singh et al, 2014;Taha, 2015;Zachariadis and Kouvaritakis, 2003;Yumino et al, 2015). Having ratified the Kyoto Protocol, the Convention on Long-Range Transboundary Air Pollution (CLRTAP) and other international acts, the Russian Federation confirmed its adherence to the concept of sustainable development and its intention to produce a considerable reduction in air pollutants and greenhouse gas (GHG) emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The automated control system (ACS) for the active rectifier was built on the basis of an integrated regulator with the subsequent pulse-width modulation [42,43]. The designed ACS ensures the predefined dynamics of change in the charging voltage and current under the CC-CV modes.…”
Section: A Simulation Model Of the Proposed Charging Stationmentioning
confidence: 99%
“…Moreover, drives with less idle events have less opportunity for the exhaust to cool down and therefore challenge the after-treatment systems less. After-treatment systems operate optimally within a specific temperature range [40]. Therefore, it could be concluded that there is significant advantage in ensuring a route has the least opportunity for idle events as the regulation allows.…”
Section: Vehicle Dynamicsmentioning
confidence: 99%